Fatigue and recovery among Malaysian doctors: the role of work-related activities during non-work time - Mohd Fadhli Mohd Fauzi; Hanizah Mohd Yusoff; Nur Adibah Mat Saruan; Rosnawati Muhamad Robat; Mohd Rizal Abdul Manaf; Maisarah Ghazali (BMJ Open)
Objectives This paper aims to estimate the level of acute fatigue, chronic fatigue and intershift recovery among doctors working at public hospitals in Malaysia and determine their inter-relationship and their association with work-related activities during non-work time.Design Cross-sectional.Setting Seven core clinical disciplines from seven tertiary public hospitals in Malaysia.Participants Study was conducted among 330 randomly-sampled doctors. Response rate was 80.61% (n=266).Results The mean score of acute fatigue, chronic fatigue and intershift recovery were 68.51 (SD=16.549), 54.60 (SD=21.259) and 37.29 (SD=19.540), respectively. All these scores were out of 100 points each. Acute and chronic fatigue were correlated (r=0.663), and both were negatively correlated with intershift recovery (r=−0.704 and r=−0.670, respectively). Among the work-related activities done during non-work time, work-related ruminations dominated both the more frequent activities and the association with poorer fatigue and recovery outcomes. Rumination on being scolded/violated was found to be positively associated with both acute fatigue (adjusted regression coefficient (Adj.b)=2.190, 95% CI=1.139 to 3.240) and chronic fatigue (Adj.b=5.089, 95% CI=3.876 to 6.303), and negatively associated with recovery (Adj.b=−3.316, 95% CI=–4.516 to –2.117). Doing work task at workplace or attending extra work-related activities such as locum and attending training were found to have negative associations with fatigue and positive associations with recovery. Nevertheless, doing work-related activities at home was positively associated with acute fatigue. In terms of communication, it was found that face-to-face conversation with partner did associate with higher recovery but virtual conversation with partner associated with higher acute fatigue and lower recovery.Conclusions Work-related ruminations during non-work time were common and associated with poor fatigue and recovery outcomes while overt work activities done at workplace during non-work time were associated with better fatigue and recovery levels. There is a need for future studies with design that allow causal inference to address these relationships.